The Relationship between Injectable Contraception and Body Mass Index (BMI) and Amenorrhea - Ayu Nina MIrania; Stephanie Lexy Louis; Evi Yuniarti (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Indonesian government has established a Family Planning policy to regulate the distance and age of birth in the hope of reducing the problem of population density which can result in various problems in Indonesia. One type of contraception that is an option is hormonal birth control in the form of injections, both 1-month and 3-month injections. The use of hormonal contraceptives has various risk factors, including weight gain and menstrual cycle disorders. The purpose of this study was to determine the effect of the relationship between 3-month contraception and body mass index (BMI) and the incidence of amenorrhea. This type of research is an analytical survey with a cross sectional approach. The sample in this study was taken using a purposive sampling technique that was in accordance with the inclusion and exclusion criteria. Data collection techniques by distributing questionnaires, interviews and measuring weight and height. The analysis used the Chi Square test and obtained a p value of 0.000, OR=15,0 on duration of contraception with Body Mass Index and p value of 0,001, OR=0,20 on amenorrhea. The conclusion of this study shows that there is an effect of the duration of 3 months of contraceptive use on body mass index and amenorrhea. Therefore it is hoped that health workers and acceptors can always communicate, especially regarding the side effects of contraception